Aqidah dan Etika: Membangun Moralitas di Tengah Perubahan Sosial - Nashirah Dwi Arini Faiza; Tia Angrelia; Siti Nuriyah Ahmad; Risya Purnama Sari; Wismanto Wismanto; Fitria Mayasari (Reflection : Islamic Education Journal, 2025)
The background of this study is the increasingly rapid social, cultural, and technological changes that have an impact on the dynamics of morality in society. In the midst of these changes, aqidah (belief) and ethics become important foundations in building solid morality. However, the main challenge faced is how to maintain the relevance of the teachings of aqidah and ethics in the context of modern life that continues to develop. This study aims to analyze the role of aqidah and ethics in shaping individual and collective morality amidst changing times. The main objective is to understand how religious beliefs and ethical principles can be applied effectively in maintaining moral integrity amidst the rapid flow of global change. The method used in this study is a qualitative method with analysis carried out by looking at the relationship between the values of aqidah, ethics, and morality in everyday life. The results of the study show that aqidah and ethics have an important role in shaping resilient morality amidst change. A deep understanding of aqidah and the application of ethical principles have proven to be a foundation for society to maintain positive moral values. However, the results also show that adaptation and renewal in the approach to teaching aqidah and ethics are needed to be more relevant and accepted by the younger generation living in the digital era.